Efficacy of a novel bivalent vaccine containing porcine circovirus type 2d and Mycoplasma hyopneumoniae against a dual PCV2d and Mycoplasma hyopneumoniae challenge - Ham, Sehyeong; Suh, Jeongmin; Oh, Taehwan; Kim, Chonghan; Seo, Byoung-Joo; Chae, Chanhee (Frontiers in Veterinary Science, 2023)
The purpose of this study was to evaluate a novel inactivated bivalent porcine circovirus type 2d (PCV2d) and Mycoplasma hyopneumoniae single-dose vaccine for efficacy under experimental conditions. A 2.0 mL dose of bivalent vaccine was administered intramuscularly to pigs at 21 days of age in accordance with the manufacturer's instructions. The pigs were challenged at 42 days of age either intranasally with PCV2d, or intratracheally with M. hyopneumoniae, or with both. Vaccinated-challenged pigs improved the growth performance compared to pigs that were unvaccinated and then, challenged. Vaccinated-challenged pigs elicited a significant amount of protective immunity for PCV2d-specific neutralizing antibodies and interferon- secreting cells (IFN--SC) as well as for M. hyopneumoniaespecific IFN--SC compared to unvaccinated/challenged pigs. Induction of systemic cellular and humoral immune responses from bivalent vaccination reduced the viral and mycoplasmal loads in the blood and larynx. Vaccination and challenge simultaneously reduced both lung and lymphoid lesion severity when compared to unvaccinated-challenged pigs. The results of this study demonstrated that the evaluated bivalent PCV2d and M. hyopneumoniae vaccine was efficacious in protecting pigs from the most predominant PCV2d genotype in the field today, as evaluated with a dual PCV2d and M. hyopneumoniae challenge under experimental conditions.